1992
DOI: 10.1148/radiographics.12.6.1439020
|View full text |Cite
|
Sign up to set email alerts
|

Congenital malformations of the cervicothoracic lymphatic system: embryology and pathogenesis.

Abstract: Familiarity with the embryology of the lymphatic system is helpful in understanding the pathogenesis and radiologic appearance of lymphangiomas of the cervicothoracic region. By considering anatomic location and radiologic appearance, one can predict the type of lymphangioma present, the primordial lymph sac from which the malformation arose, and when it formed in embryonic life. Cystic hygromas are composed of large, dilated lymphatic spaces. They form when a primordial lymph sac fails to reestablish communic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
88
0
8

Year Published

1994
1994
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(98 citation statements)
references
References 0 publications
2
88
0
8
Order By: Relevance
“…However, lymphatic vessels were difficult to identify, because no specific markers are available for them. Since the beginning of the 20th century, three different theories concerning the origin of the lymphatic system have been presented (11,35,36). The most widely accepted theory was proposed by Florence Sabin (10), who suggested that during the fetal period lymphatic structures sprout from large central veins in certain locations to form the primordial lymph sacs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, lymphatic vessels were difficult to identify, because no specific markers are available for them. Since the beginning of the 20th century, three different theories concerning the origin of the lymphatic system have been presented (11,35,36). The most widely accepted theory was proposed by Florence Sabin (10), who suggested that during the fetal period lymphatic structures sprout from large central veins in certain locations to form the primordial lymph sacs.…”
Section: Discussionmentioning
confidence: 99%
“…The most widely accepted theory was proposed by Florence Sabin (10), who suggested that during the fetal period lymphatic structures sprout from large central veins in certain locations to form the primordial lymph sacs. Subsequently, the sacs enlarge, coalesce, and form new sprouts, which grow into the periphery of the embryo (11,12,35,36).…”
Section: Discussionmentioning
confidence: 99%
“…The origin of lymphangiomas is controversial; they may be developmental [9,10], hamartomatous [ii], or neoplastic [12]. At least 90% of lymphangiomas manifest as a mass in the neck or axilla in patients less than 2 years old [9], with a reported male predominance [1 3].…”
Section: Discussionmentioning
confidence: 99%
“…Uncommonly, they are also described in other sites, such as the mediastinum (5%), axilla (20%), abdominal cavity (in the colon, liver and spleen), retroperitoneum (in the kidneys), scrotum and, very rarely, in the skeletal system [25,26].…”
Section: Figmentioning
confidence: 99%